Reflections from the Field: Disparate responses to labour exploitation in post-Katrina Louisiana - McCallum, Leanne (Anti-Trafficking Review, 2020)
Hurricane Katrina was a devastating natural disaster that changed the landscape of the United States’ Gulf Coast. This was followed by a human-made disaster of failed policies, poor governmental oversight, and rampant labour abuse. This article compares how the anti-trafficking and labour rights movements responded to the widespread labour abuse following Katrina. It examines how the worker rights movement responded to systemic issues impacting labourers, and explores the anti-trafficking movement’s criminal justice response to severe forms of exploitation. It shows how the anti-trafficking movement failed to adequately address severe forms of labour abuse, as opposed to the more successful organising efforts of the worker rights movement. The article concludes by considering how the two movements may respond to conditions of labour exploitation emerging as a result of a new disaster impacting workers in Louisiana: the COVID-19 pandemic.